Structural studies of a mannoglucan from Cremastra appendiculata (Orchidaceae) by chemical and enzymatic methods. (15th November 2021) - Zhang, Xue; Bi, Caili; Shi, Hongcan; Li, Xiaojun
Abstract: Pseudobulb of Cremastra appendiculata (Orchidaceae) is a traditionally used medicine in China for treatment of certain cancers. The polysaccharides from this medicinal plant are poorly understood. Therefore, we focused on the isolation and fine structure characterization of C. appendiculata polysaccharides. After isolation by DE-52 and Superdex 200 gel chromatography, the purified polysaccharide (named as CAP) with Mw 557.5 kDa was obtained with a narrow and symmetric peak presented in the HPGPC. The monosaccharide composition results showed in HPAEC that CAP was a heteropolysaccharide composed of glucose and mannose at a molar ratio roughly 0.34:0.66. The methylation results indicated that CAP was a 1, 4-β-mannose and 1, 4-β-glucose linear linkage. The further NMR studies suggested a 0.208 acetylation substitution of CAP and a hexasaccharide repeating unit composed of 1, 4-β-mannose and1, 4-β-glucose in the CAP structure. The chemical structure of CAP was confirmed further by the specific glucanase and mannanase hydrolysis results. Highlights: A polysaccharide (CAP) was isolated from Pseudobulb of Cremastra appendiculata . The average molecular weight of the CAP is about 557.5 kDa. Structure of CAP was deduced by methylation, NMR and enzymatic hydrolysis results. CAP is a linear mannoglucan with 1, 4-β-mannose and 1, 4-β-glucose interlace linked. CAP with 0.208 of DA showed certain bioactivities on RAW 264.7 cells.